Echocardiographic in pulmonary hypertension: evaluation of the right heart chambers and pulmonary artery - Serra, Catarina (2022)
Introduction: Pulmonary Hypertension (PH) is defined as an increase in mean pulmonary artery (PA) pressure above 25mmHg at rest and an increase of 30mmHg with exertion. In more advanced pathological stages, structural changes may occur in the cardiac chambers due to hemodynamic changes. Objectives: To verify if PH patients present with right-side hemodynamic and structural changes. Material and Methods: The study was carried out using a database of the cardiology service of a local health unit in the central region of mainland Portugal. Patients studied were those with PH and those without PH. Although patients with PH were included, those presenting with uncontrolled arterial hypertension, diabetes mellitus and/or congenital cardiac alterations were excluded. Results: The sample consisted of 113 individuals, of which 35 had PH (31.0%) and 68 did not have PH (69.0%). It was observed that in the group with PH there was a growing increase in the cardiac chambers and PA. It was also observed that the higher the Pulmonary Artery Systolic Pressure (PASP), the higher the value obtained in the cardiac chambers and PA. There was also a decrease in the tricuspid annular plane systolic excursion (TAPSE) value as a function of the increase in PASP, compared to lower values. The tricuspid regurgitation velocity (TRV) did not increase much in regards to the increase in PASP, with a greater accentuation of the 2.9-3.4m/s parameter in this correlation. Conclusion: Our study verified that structural and hemodynamic changes in the right heart chambers and PA occur in the presence of PH.